Social Protection for Informal Sector Workers: Challenges and Innovations of BPJS Employment in Indonesia - Br.Tobing, Dina Khairunisa; Sitorus , Natalia Fransiska; Sinaga, Nellyana Dwi Putri; Hutagalung, Enjelito (PT. Anagata Sembagi Education, 2026)
This study examines the challenges and innovations of BPJS Employment in providing social protection for informal sector workers in Indonesia. Informal workers face various obstacles, including low awareness of social security benefits, unstable income, limited program outreach, and difficulties accessing registration offices. The research uses a qualitative case study approach, employing primary data through interviews with informal workers and BPJS Employment officers, as well as secondary data from official documents, reports, and relevant literature. The results indicate that innovations such as flexible contribution schemes, online registration, and community-based outreach successfully increase participation among informal workers and positively impact their welfare, both financially and psychologically. These findings highlight the importance of adaptive and inclusive policy strategies that leverage digital technology and community approaches to effectively reach informal workers. This study provides recommendations for BPJS Employment and policymakers in designing more responsive social protection programs for informal sector workers in Indonesia.